2014
DOI: 10.1242/dev.112367
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid controls body axis extension by directly repressing Fgf8 transcription

Abstract: Retinoic acid (RA) generated in the mesoderm of vertebrate embryos controls body axis extension by downregulating Fgf8 expression in cells exiting the caudal progenitor zone. RA activates transcription by binding to nuclear RA receptors (RARs) at RA response elements (RAREs), but it is unknown whether RA can directly repress transcription. Here, we analyzed a conserved RARE upstream of Fgf8 that binds RAR isoforms in mouse embryos. Transgenic embryos carrying Fgf8 fused to lacZ exhibited expression similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 41 publications
6
121
0
Order By: Relevance
“…Previous studies demonstrated that the repressive Fgf8 RARE recruits the RA receptor (RAR) (Kumar and Duester, 2014), but recruitment of its heterodimer partner RXR had not been analyzed. Here, we used chromatin immunoprecipitation (ChIP) on E8.25 mouse embryo trunk tissue to show that the Fgf8 RARE recruits RXRa as does the Rarb RARE (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that the repressive Fgf8 RARE recruits the RA receptor (RAR) (Kumar and Duester, 2014), but recruitment of its heterodimer partner RXR had not been analyzed. Here, we used chromatin immunoprecipitation (ChIP) on E8.25 mouse embryo trunk tissue to show that the Fgf8 RARE recruits RXRa as does the Rarb RARE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As caudal progenitor cells migrate to the developing trunk during body axis extension, their Fgf8 chromosomal locus becomes located more peripherally in the nucleus (a location associated with repression), plus this shift to the nuclear periphery requires RA generated by Raldh2 (Patel et al, 2013). Analysis of wild-type and mutant bacterial artificial chromosome transgenes carrying the mouse Fgf8 locus fused to lacZ demonstrated that a conserved RARE was able to restrict Fgf8-lacZ expression to the caudal progenitors of mouse embryos; also, chromatin immunoprecipitation studies on wild-type and Raldh2−/− embryos showed that Polycomb repressive complex 2 (PRC2) and the repressive H3K27me3 mark are recruited near the Fgf8 RARE in an RA-dependent manner (Kumar and Duester, 2014). These studies suggest that RA directly represses Fgf8 transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, both RAdeficient chick embryos and mouse Raldh2 Ϫ/Ϫ embryos exhibit ectopic Fgf8 expression extending from the caudal progenitor zone into the trunk that disrupts somitogenesis (67,68). Recently, it has been demonstrated that RA controls mouse somitogenesis by directly repressing Fgf8 transcription through binding to the RARE (RA response element) in the regulatory sequence of Fgf8 (69). By analyzing the 6,000-bp sequences upstream of the fgf8a transcription start site (ENS-DARG00000003399) using MatInspector, as we reported previously (44), we find that zebrafish fgf8a has a presumptive DR5 RARE with the core sequences of TTGTTGATCAGGCAAT-GAGCAACAG located between Ϫ3,857 and Ϫ3,833 bp, positioned in the reverse direction.…”
Section: ;Foxc2mentioning
confidence: 91%
“…FGF signalling is inhibited by the RA pathway (and vice versa), and this mutual inhibition controls A-P patterning and mesodermal differentiation during axis extension (del Corral et al, 2003;Dorey and Amaya, 2010). Indeed, a recent study demonstrated that RA represses the transcription of Fgf8 (Kumar and Duester, 2014), whereas Cyp26a1 expression is not affected by the lack of Fgfr1 (Wahl et al, 2007;Martin and Kimelman, 2010).…”
Section: Cyp26a1mentioning
confidence: 99%